Differences in Family Planning and Fertility Among Female and Male Gynecologic Oncologists - Mihae Song; Katelyn Tessier; Jani Jensen; Phoebe Leonard; Melissa A. Geller; Deanna Teoh (Mary Ann Liebert, 2021)
Background: The objective of the study was to compare family planning and infertility among female and male gynecologic oncologists in the United States Methods: This cross-sectional multiple choice survey was administered to the Society of Gynecologic Oncology gynecologic oncologists. The survey collected information on demographics and practice, family planning, and fertility and infertility experiences. Chi-square and Fisher's exact tests were used to compare experiences by gender. Results: Two hundred eighteen of 1243 (18%) members responded to the survey. The majority were women (71%), Caucasian (78%), and had been practicing fewer than 10 years (56%). One-third (32%) were 35+ years of age at the birth of their first child, and 67% delayed childbearing due to their career. Women were more likely than men to report career choice-influenced family planning. Just under half (44%) expressed current or past concerns about fertility, and this was more prevalent among women; 81% had sought infertility counseling. Among respondents who had fertility struggles, almost half (45%) reported their colleagues were unaware. Forty percent felt their fertility concerns affected work life, and 13% felt stigmatized for their fertility struggles. Conclusions: These findings suggest that a career in gynecologic oncology have an impact on family planning, often resulting in childbearing delays and infertility concerns, especially among women. Support for our colleagues struggling with infertility should be included in wellness initiatives.